Unilateral Spinal Anaesthesia in Calves - YAYLA, S.; KILIC, E.; AYDIN, U.; OZAYDIN, I.; BARAN, V.; KAMILOGLU, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
In this study, we aimed to evaluate the effects of unilateral anaesthesia by the administration of hyperbaric bupivacaine through the lumbosacral space into the subarachnoid space in calves. A total of 10 calves with unilateral femoral fractures were included in the study. After each calf was placed in a lateral position on the side intended for surgery, 15 mg of hyperbaric bupivacaine was slowly injected into the subarachnoid space. The onset, duration and depth of anaesthesia were determined by the pinprick test (scale 1–4). In addition, heart rate, diastolic arterial blood pressure, systolic arterial blood pressure, mean arterial blood pressure, respiratory rate and body temperature of the calves were monitored and recorded from the onset to 120 min after anaesthesia. The onset of unilateral spinal anaesthesia was within 20 s and the mean duration of anaesthesia was 155.40 min. Although there were statistical differences between hemodynamic values in the study, they were within the reference values. As a result, we believe that unilateral spinal anaesthesia in calves provides adequate anaesthesia for use in orthopaedic procedures; thus, it can be used in practice.